2016
DOI: 10.1158/0008-5472.can-15-2333
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibition of the Histone Lysine Demethylase KDM1A Suppresses the Growth of Multiple Acute Myeloid Leukemia Subtypes

Abstract: Lysine-specific demethylase 1 (KDM1A) is a transcriptional coregulator that can function in both the activation and repression of gene expression, depending upon context. KDM1A plays an important role in hematopoiesis and was identified as a dependency factor in leukemia stem cell populations. Therefore, we investigated the consequences of inhibiting KDM1A in a panel of cell lines representing all acute myelogenous leukemia (AML) subtypes using selective, reversible and irreversible KDM1A smallmolecule inhibit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 50 publications
6
83
1
Order By: Relevance
“…Treatment of AML cell lines and a xenograft model with the cyclopropylaminebased irreversible KDM1A inhibitor RN-1 led to inhibition of tumor cell growth and increased cellular differentiation. 27 Another study found the combination treatment of an irreversible KDM1A inhibitor T-3775440 with the neural precursor cell expressed, developmentally down-regulated 8-activating enzyme inhibitor pevonedistat resulted in synergistic growth inhibition of AML cells and improved survival in a tumor xenograft model of AML. 28 The KDM1A inhibitor ORY-1001 was investigated in a multicenter phase I study in relapsed or refractory acute leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of AML cell lines and a xenograft model with the cyclopropylaminebased irreversible KDM1A inhibitor RN-1 led to inhibition of tumor cell growth and increased cellular differentiation. 27 Another study found the combination treatment of an irreversible KDM1A inhibitor T-3775440 with the neural precursor cell expressed, developmentally down-regulated 8-activating enzyme inhibitor pevonedistat resulted in synergistic growth inhibition of AML cells and improved survival in a tumor xenograft model of AML. 28 The KDM1A inhibitor ORY-1001 was investigated in a multicenter phase I study in relapsed or refractory acute leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Upon LSD1 inhibition and ATRA treatment, the expression of genes associated with myeloid differentiation was upregulated with a concomitant increase of H3K4me2 levels at these genes. LSD1 inhibitor exerts synergistic effects with other anti‐cancer agents, such as Ara‐C or an inhibitor of H3K27 methyltransferase, on the induction of AML cell death, indicating the multifaceted function of LSD1 . Moreover, Harris et al .…”
Section: Molecular Structure and Function Of Lysine‐specific Demethylmentioning
confidence: 94%
“…LSD1 inhibitor exerts synergistic effects with other anti-cancer agents, such as Ara-C or an inhibitor of H3K27 methyltransferase, on the induction of AML cell death, indicating the multifaceted function of LSD1. (39) Moreover, Harris et al report the contribution of LSD1 in maintaining stem cell properties in a subtype of AML harboring an MLL gene translocation. (40) Increased expression of LSD1 was detected in MLL-mutant leukemia cells, especially in cells expressing the MLL-AF9 fusion protein, which acts as an oncogenic transcriptional regulator.…”
mentioning
confidence: 99%
“…Meanwhile, several reversible LSD1 inhibitors have been reported in recent years, most of which were discovered by basic strategies for drug discovery such as high‐throughput screening and hit‐to‐lead optimization. As shown in Figure , reversible inhibitors 8–11 are structurally diverse [e. g., N ′ ‐(1‐phenylethylidene) benzohydrazides in 8 , dithiocarbamates in 9 , 3, 5‐diamino‐1,2,4‐triazole in 10 , and pyridine in 11 ] . Reversible LSD1 inhibitors also show various inhibition types, such as competitive in 10 , non‐competitive in 8 , and cofactor competitive in 9 , which were revealed by enzymology analysis.…”
Section: Introductionmentioning
confidence: 99%